An evolutionary approach to the climate change negotiation game - Pierre Courtois; Jean Christophe Péreau; Tarik Tazdaït (Fondazione Eni Enrico Mattei (FEEM), 2001)
We describe in this paper an evolutionary game theoretic model aiming at representing the climate change negotiation. The model is used to examine the outcome of climate change negotiations in a framework which seeks to closely represent negotiation patterns. Evolutionary setting allows us to consider a decision making structure characterised by agents with bounded knowledge practising mimics and learning from past events and strategies. We show on that framework that a third significant alternative to the binary coordination-defection strategies needs to be considered: a unilateral commitment as precautionary strategy. As a means to widen cooperation, we examine the influence of linking environmental and trade policies via the implementation of a trade penalty on non cooperative behaviours.
Keywords: D74; Q28; 330; Environmental negotiation; coalition; precautionary unilateral commitment; evolutionary process; Klimaschutz; Umweltabkommen; Verhandlungen; Evolutionäre Spieltheorie